Determinants of nurse job dissatisfaction - findings from a cross-sectional survey analysis in the UK - Michaela Senek; Steven Robertson; Tony Ryan; Rachel King; Emily Wood; Bethany Taylor; Angela Tod (BMC, 2020)
Abstract Background A lower recruitment and high turnover rate of registered nurses have resulted in a global shortage of nurses. In the UK, prior to the COVID-19 epidemic, nurses' intention to leave rates were between 30 and 50% suggesting a high level of job dissatisfaction. Methods In this study, we analysed data from a cross-sectional mixed-methods survey developed by the Royal College of Nursing and administered to the nursing workforce across all four UK nations, to explore the levels of dissatisfaction and demoralisation- one of the predictors of nurses' intention to leave. We carried out logistic regression analysis on available data in order to determine what impacts job dissatisfaction. Results In total, 1742 nurses responded to questions about working conditions on their last shift. We found that nearly two-thirds of respondents were demoralised. Nurses were five times more likely (OR 5.08, 95% CI: 3.82-6.60) to feel demoralised if they reported missed care. A perceived lack of support had nearly the same impact on the level of demoralisation (OR 4.8, 95% CI: 3.67-6.38). These findings were reflected in the qualitative findings where RNs reported how staffing issues and failures in leadership, left them feeling disempowered and demoralised. Conclusion A large proportion of nurses reported feeling dissatisfied and demoralised. In order to reduce the negative impact of dissatisfaction and improve retention, more research needs to investigate the relationship dynamics within healthcare teams and how the burden experienced by RNs when unsupported by managers impacts on their ability to provide safe, good-quality care. These findings predate the current Covid-19 pandemic outbreak which may have had a further detrimental effect on job satisfaction in the UK and other nation's nursing workforce.